Pandangan Model Dua-Sektor Lewis dan Model Solow terhadap Pertumbuhan Ekonomi Indonesia - Hendiva Tri Nugraha; Masruri Muchtar; Pardomuan Robinson Sihombing (Ecoplan, 2023)
This study aims to acknowledge the effect of applying the two-sector Lewis and Solow neoclassical growth model in Indonesia’s economic growth. The variables are Urbanization Rate, Labor in Industry Sector, Human Development Index, Total Factor Productivity, and GDP. The research model is an associative quantitative method with multiple linear regression on time series data. The result showed that all variables simultaneously affect GDP significantly. Urbanization (partially) affects GDP positively and significantly. Labor in Industry Sector (partially) doesn’t affect GDP. HDI doesn’t affect GDP. TFP affects GDP positively and considerably at a 90% confidence level. According to this research, the Indonesian Government should increase the quality of their labor, especially in the industry sector. Further research is expected to add more variables that represent both models.